Measurement and Correlation for Solubility of Diosgenin in Some Mixed Solvents - 陈飞雄 赵明蕊 冯露 任保增 (中国化学工程学报：英文版, 2014)
The solubility data of diosgenin in mixed systems of ethanol+1-propanol (1︰1), ethanol+1-butanol (1︰1), ethanol+isobutyl alcohol (1︰1), methanol+isobutyl alcohol (1︰1), methanol+isobutyl alcohol (1︰4), ethanol+1-pentanol (1︰1) and carbon tetrachloride were measured over the temperature range from 289.15 K to 334.15 K by a laser monitoring observation technique at atmospheric pressure, with all mixtures mixed by volume ratio. The Apelblat equation, the ideal solution model, and theλh equation are used to correlate the solubility data. The results show that the three models agree well with the experimental data, providing essential support for industrial design and further theoretical study.